2020
DOI: 10.1093/jas/skaa144
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of endometritis and cystitis in sows: use of biomarkers

Abstract: The health status of breeding sows is critical for physiological reproductive performance in the herd and has a major impact on animal welfare, as well as on the economic output of a farm. Diseases of the urogenital tract in particular, such as endometritis and cystitis, occur on farms characterized by low reproductive performance. It is very important to recognize and treat the causes of these as soon as possible, and consequently a range of biomarkers have been used and described. This article summarizes tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 46 publications
0
26
0
2
Order By: Relevance
“…Proteinuria, the presence of abnormal protein level in urine, is a consequence of either abnormal transglomerular passage of proteins, because of increased permeability of glomerular capillary wall and their subsequent impaired reabsorption by the epithelial cells of the proximal tubuli [51], or the consequence of urea breakdown by bacteria in an alkaline environment (urine pH > 8). Grahofer et al (2020) in their recent report of biomarkers for diagnosis of cystitis in sows, identified and proposed the presence of proteinuria as one of the most reliable and sensitive urinalysis biomarkers, in comparison to the gold standard of histopathology. In human medicine, Carter et al (2006) [52] also reported an association between proteinuria and bacteriuria but the causative relationship remained undefined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Proteinuria, the presence of abnormal protein level in urine, is a consequence of either abnormal transglomerular passage of proteins, because of increased permeability of glomerular capillary wall and their subsequent impaired reabsorption by the epithelial cells of the proximal tubuli [51], or the consequence of urea breakdown by bacteria in an alkaline environment (urine pH > 8). Grahofer et al (2020) in their recent report of biomarkers for diagnosis of cystitis in sows, identified and proposed the presence of proteinuria as one of the most reliable and sensitive urinalysis biomarkers, in comparison to the gold standard of histopathology. In human medicine, Carter et al (2006) [52] also reported an association between proteinuria and bacteriuria but the causative relationship remained undefined.…”
Section: Discussionmentioning
confidence: 99%
“…Kauffold et al (2010), using ultrasonography, reported that sows with UTI, defined on the basis of high bacterial count and macroscopic/biochemical urine abnormalities, were more likely to have high or moderate amounts of sediment in urine than those without UTI. Recently, Grahofer et al (2020), also concluded that evaluation of presence of sediment is useful to detect sows with cystitis and bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kauffold et al, (2010) reported, using ultrasonography, that sows with UTI, de ned by high bacterial count and macroscopic/biochemical urine abnormalities, were more likely to have high or moderate amounts of sediment in urine than those without UTI. Recently, Grahofer et al (2020), also concluded that evaluation of presence of sediment is useful to detect sows with cystitis and bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that post-partum vaginal discharge occurred frequently in healthy and diseased animals [7][8][9][10][11][12][13], with the highest incidence between day 2 and 4 post-partum. Physiological vaginal discharge, which is watery or slightly cloudy, can be observed immediately after parturition [14][15][16][17]. An increased volume of vaginal discharge in sows is associated with endometritis, but there is no association between the occurrence of endometritis and the colour of the vaginal discharge [14,17].…”
Section: Introductionmentioning
confidence: 99%